(untitled) (Archives of Pediatrics of Uruguay, 2021)
Background: nutrition during pregnancy impacts the foetus and the newborn health, it has consequences at the epigenetic level and determines long-term neurological consequences. Iron requirements during pregnancy are estimated at 27 mg/day. Iron is blood absorption from is most efficient from beef. Umbilical cord blood ferritin levels can be used to assess iron deposits reached during the foetal stage. Ferritin levels are linked to the child’s long-term development. Objective: this exploratory study’s objective is to determine the relationship between beef consumption during the first quarter of pregnancy and ferritin levels in the umbilical cord. Methods: we carried out a descriptive, observational study with prospectively collected data for one-year at the Neonatology Department of the Pereira Rossell Hospital Center (CHPR) in Montevideo, Uruguay. A total of 188 patients met the inclusion criteria. We extracted umbilical cord blood after a strict cord clamping after one minute of life. Ferritin was measured using the chemoimmunofluorescence method. We carried out a maternal nutritional survey using a qualitative-quantitative method and measured the frequency and approximate quantity of iron source food consumption during the last quarter of pregnancy. This survey was focused on maternal beef consumption as the major heme iron source in Uruguay. We analyzed the relationship between these variables. Results: latent iron deficiency (ferritin in the umbilical cord <100 ng / ml) was associated with lower beef consumption during pregnancy. Fisher p-value: 0.0133, OR: 3.71, 95% CI (1.25 - 11.05). Conclusions: this study agrees with the evidence that shows that low levels of total iron and beef consumption during pregnancy determine an increased risk of latent iron deficiency and lower levels of ferritin in newborns, and therefore, greater risk of long-term adverse effects on myelination and neurocognitive development.